2014
DOI: 10.1167/iovs.13-13693
|View full text |Cite
|
Sign up to set email alerts
|

Generational Difference of Refractive Error and Risk Factors in the Handan Offspring Myopia Study

Abstract: Citation: Lin Z, Gao TY, Vasudevan B, et al. Generational difference of refractive error and risk factors in the Handan Offspring Myopia Study. Invest Ophthalmol Vis Sci. 2014;55:5711-5717. DOI:10.1167/ iovs.13-13693 PURPOSE. To report the refractive error difference (RED) between parents and their children, and its risk factors, in a rural area of China.METHODS. Children (6-17 years) and their parents (36.2 6 4.1 years) from the Handan Offspring Myopia Study (HOMS) were enrolled. Cycloplegic autorefracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…All these studies, including investigations assessing differences in refractive error between parents and their children, agree on the considerable increase in the prevalence of myopia. 28 As in previous studies, factors associated with myopia in our study were older age, parental myopia, and time spent outdoors. [29][30][31] Interestingly, the prevalence of high myopia (refractive error À6.00 and À8 D) was not significantly associated with the time spent outdoors in our study.…”
Section: Discussionsupporting
confidence: 76%
“…All these studies, including investigations assessing differences in refractive error between parents and their children, agree on the considerable increase in the prevalence of myopia. 28 As in previous studies, factors associated with myopia in our study were older age, parental myopia, and time spent outdoors. [29][30][31] Interestingly, the prevalence of high myopia (refractive error À6.00 and À8 D) was not significantly associated with the time spent outdoors in our study.…”
Section: Discussionsupporting
confidence: 76%
“…[1][2][3][4][5][6] In the baseline report of the Beijing Myopia Progression Study (BMPS), we demonstrated that the generational myopic shift from parents to their children was approximately 2 diopters (D) and 1D in urban and rural Chinese students, respectively. 7,8 These data provide support that lifestyle and exposure to environmental factors contribute to the development of myopia. Among the environmental factors, daily activities such as near work and outdoor activities are generally thought to be key factors associated with myopic onset and/or its progression.…”
Section: Introductionmentioning
confidence: 62%
“…In the current study, the rural students who performed the eye exercises in school had less myopic refractive error as compared to the urban students (-0.40D vs. -1.70D). Moreover, as compared to urban students, the rural students are exposed to relatively low risk factors for myopia, such as spending less time on near work and more time on outdoor activities, having a more open and spacious living environment, and having fewer myopic parents [2124]. Lastly, urban student’s myopia and related near oculomotor imbalance may be more “embedded” in those with intensive near work demands, and thus less susceptible to any remediation/intervention [25].…”
Section: Discussionmentioning
confidence: 99%